2005
DOI: 10.1152/ajpcell.00322.2004
|View full text |Cite
|
Sign up to set email alerts
|

Expression of granulocyte colony-stimulating factor is induced in injured rat carotid arteries and mediates vascular smooth muscle cell migration

Abstract: Granulocyte colony-stimulating factor (G-CSF) is a lineage-restricted hematopoietic growth factor that stimulates proliferation and maturation of hematopoietic progenitors and is a known powerful mobilizer of bone marrow-derived stem cells. Very little has been reported on G-CSF expression and modulation of vascular smooth muscle cell (VSMC) activation. The purpose of this study was to characterize the expression and effects of G-CSF on primary human VSMC and balloon angioplasty-injured rat carotid arteries. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 43 publications
(45 reference statements)
0
15
0
Order By: Relevance
“…VSMC in uninjured arteries do not express G-CSF, but in response to injury or cytokine stimulation, VSMC are capable of G-CSF expression [38]. We have previously shown that over-expression of AIF-1 in human VSMC can induce G-CSF expression and secretion [12].…”
Section: Discussionmentioning
confidence: 99%
“…VSMC in uninjured arteries do not express G-CSF, but in response to injury or cytokine stimulation, VSMC are capable of G-CSF expression [38]. We have previously shown that over-expression of AIF-1 in human VSMC can induce G-CSF expression and secretion [12].…”
Section: Discussionmentioning
confidence: 99%
“…These results triggered an alert for G-CSF treatments. It has been reported that G-CSF could activate and induce the proliferation of vascular smooth muscle cells in injured arteries [76,77]. Increased neointimal formation and in-stent restenosis in coronaries treated with bare, but drug-eluting stents were observed in G-CSF-treated pigs submitted to myocardial infarction [78].…”
Section: Clinical Studiesmentioning
confidence: 98%
“…29 It has been demonstrated that the expression of G-CSF is induced in the local arterial wall by injury. 30 Thus, endogenous G-CSF production by stentinduced injury might also contribute to mobilization of CD34-positive cells and restenosis.…”
Section: Circulation February 6 2007mentioning
confidence: 99%